Validation of soil moisture derived from water balance method and satellite observation - CHATTOPADHYAY, N.; VYAS, S. S.; BHATTACHARYA, B. K.; TIDKE, N. S.; DHANGAR, N. G. (MAUSAM, 2017)
Under the present study estimation of high resolution soil moisture (SM) under Pan India mode using simple water balance method and from satellite data has been explored. It aims at the simple calculation of soil moisture followed by verification with ground truth data of SM on spatial and temporal scale (WC) as climatic input. The model has been verified for winter (January-February), pre-monsoon (March-May), monsoon (June-September) and post-monsoon (October-December) seasons of year 2013. The comparison of model estimates with the in-situ data from 17 ground stations (for 396 paired datasets) over different seasons produced a better correlation coefficient varying from 0.46 to 0.60. The spatial comparison of SM estimated from model and satellite SM for the monsoon season shows a greater degree of coherence over most parts of India. Model derived weekly gridded SM combined with higher resolution satellite SM could use simple formulation and minimum inputs in conjunction with geographic information system (GIS). The SM is calculated on weekly basis and using gridded rainfall, potential evapotranspiration (PET) and field capacity (FC) and wilting point be used for better accuracy of the proposed block level agrometadvisory services.